GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 88 species occurrences available in GBIF matching the query: TaxonKey: Poa pratensis L. Country: South Africa. The dataset includes 88 records from 9 constituent datasets: 1 records from Phanerogamic Botanical Collections (S). 1 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 58 records from PRECIS. 1 records from Herbaria of the University and ETH Zürich. 2 records from ANTARCTIC PLANT DATABASE. 2 records from United States National Plant Germplasm System Collection. 21 records from Precis Plant Data. 1 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Royal Botanic Garden Edinburgh Herbarium (E). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences